GRAPE POMACE IMPACT ON FERMENTATIVE CHARACTERISTICS IN CONCENTRATE - García, Santiago Martínez; González, Elena Rodríguez; Richardson, Marianne Elizabeth (Contemporary Journal of Advancement in Food Science and Technology (CJAFST), 2023)
The agricultural sector in Spain is a vital component of the nation's socioeconomic framework, occupying an extensive portion of its landmass. Specifically, the livestock industry, predominantly concentrated in the Extremadura region, places Spain as the second-largest sheep-holder within the European Union. Ruminants, a significant facet of this sector, possess a digestive system adept at converting fibrous materials into crucial elements like volatile fatty acids, fermentation gases, and heat. However, within this process, methane (CH4), a potent greenhouse gas, is also produced, contributing significantly to anthropogenic CH4 emissions. Simultaneously, Spain boasts the world's largest vineyard area and ranks among the top wine producers globally. This flourishing industry yields substantial organic-rich by-products, with grape pomace accounting for approximately 20-25% of the total weight of fresh grapes, renowned for its rich polyphenolic content. In light of these factors, this study endeavors to propose environmentally sustainable strategies for the management of these agricultural practices.